Synthesis of La2Mo2O9 Nanocrystallites by Sol-Gel Process - Zhang, Quanzheng; Lu, Hongdian; Wang, Yuting; Wu, Yue; Ma, Jinjin; Zhou, Kailing; Fang, Qinyun; Ding, Dong (Asian Journal of Chemistry, 2014)
La2Mo2O9 nanocrystallites were synthesized successfully using sol-gel process with (NH4)6Mo7O24·4H2O, La(NO3)3·6H2O, citric acid and PEG400 as original materials. The result shows that spherical well-crystallized La2Mo2O9 nanoparticles were formed at 500 ºC with sizes of ca. 80 and 20 nm, which indicates the secondary nucleation exists in the reaction process. The synthesized La2Mo2O9 nanocrystallites were characterized by XRD, TEM, IR and UV-visible spectra.